2014
DOI: 10.1371/journal.pone.0091798
|View full text |Cite
|
Sign up to set email alerts
|

Species-Independent Down-Regulation of Leaf Photosynthesis and Respiration in Response to Shading: Evidence from Six Temperate Tree Species

Abstract: The ability to down-regulate leaf maximum net photosynthetic capacity (Amax) and dark respiration rate (Rdark) in response to shading is thought to be an important adaptation of trees to the wide range of light environments that they are exposed to across space and time. A simple, general rule that accurately described this down-regulation would improve carbon cycle models and enhance our understanding of how forest successional diversity is maintained. In this paper, we investigated the light response of Amax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Analysis of whether larger cells in bypass transgenics have a higher number of chloroplasts, whether the chloroplasts are larger in size, and measurements of overall RuBisCO content would be necessary to correlate the anatomical data with increased photosynthesis per unit area in the bypass plants. It also remains to be investigated whether the larger leaves in camelina bypass transgenics shade lower leaves and prevent them from reaching their highest photosynthetic potential in field conditions [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of whether larger cells in bypass transgenics have a higher number of chloroplasts, whether the chloroplasts are larger in size, and measurements of overall RuBisCO content would be necessary to correlate the anatomical data with increased photosynthesis per unit area in the bypass plants. It also remains to be investigated whether the larger leaves in camelina bypass transgenics shade lower leaves and prevent them from reaching their highest photosynthetic potential in field conditions [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional traits such as LMA are known to be sensitive to variation in light availability, with higher irradiance leading to higher LMA (Poorter et al, 2009). Intraspecific LMA variability between sunlit and shaded leaves has been shown for all three PFTs (Wyka et al, 2012;Gratani, 2014) with lower values recorded in shaded leaves and potentially leading to downregulation of gas exchange rates (Chen et al, 2014). In our study, all understory species that had no individual at the sunlit part of the canopy were sampled for trait measurements outside the plot, in sunnier places in order to reduce such environmental effects and enable between species and sites comparisons.…”
Section: Differences Between Pftsmentioning
confidence: 96%
“…This article is protected by copyright. All rights reserved environmental stresses such as droughts (e.g., Huang et al, 2019;Piao et al, 2017;Sun et al, 2015) and shade (e.g., Chen et al, 2014;Gamon & Bond, 2013). A few studies have suggested that stresses increase NPQ but reduce GPP more than SIF, leading to reduced GPP/SIF ratios (Hilker et al, 2008;Gu et al, 2019).…”
Section: Accepted Articlementioning
confidence: 99%